2021
DOI: 10.1136/gutjnl-2020-323476
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of the faecal metagenome and serum metabolome reveals the role of gut microbiome-associated metabolites in the detection of colorectal cancer and adenoma

Abstract: ObjectiveTo profile gut microbiome-associated metabolites in serum and investigate whether these metabolites could distinguish individuals with colorectal cancer (CRC) or adenoma from normal healthy individuals.DesignIntegrated analysis of untargeted serum metabolomics by liquid chromatography-mass spectrometry and metagenome sequencing of paired faecal samples was applied to identify gut microbiome-associated metabolites with significantly altered abundance in patients with CRC and adenoma. The ability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(104 citation statements)
references
References 52 publications
(56 reference statements)
2
101
1
Order By: Relevance
“…A large amount of metabolomics data has been accumulated to be used to investigate the interaction between the host and microorganisms from the perspective of metabolism. It was found that several gut microbiome-associated serum metabolites (GMSM) have changed significantly through integrated analysis of the serum metabolites and fecal metagenomics of patients with CRC and adenoma, which can efficiently discriminate patients with CRC and adenoma from normal individuals ( 108 ). Dysregulation of these metabolites indicates the possibility of common diagnostic biomarkers for CRC.…”
Section: Clinical Transformation Of the Gut Metabolome In Crcmentioning
confidence: 99%
“…A large amount of metabolomics data has been accumulated to be used to investigate the interaction between the host and microorganisms from the perspective of metabolism. It was found that several gut microbiome-associated serum metabolites (GMSM) have changed significantly through integrated analysis of the serum metabolites and fecal metagenomics of patients with CRC and adenoma, which can efficiently discriminate patients with CRC and adenoma from normal individuals ( 108 ). Dysregulation of these metabolites indicates the possibility of common diagnostic biomarkers for CRC.…”
Section: Clinical Transformation Of the Gut Metabolome In Crcmentioning
confidence: 99%
“…As far as tumor grade classification is concerned, we found that Bacteroides fragilis was significantly enriched in the colonic metaproteome of high-grade cases. This bacterial species has been found as more abundant in the CRC microbiota compared to that of the healthy controls in numerous studies, and its toxin has been hypothesized to promote colon carcinogenesis ( Boleij et al, 2015 ; Dai et al, 2018 ; Haghi et al, 2019 ; Thomas et al, 2019 ; Chen et al, 2021 ). Furthermore, among host functions, trypsin and neutral ceramidase were observed as significantly enriched in low-grade tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Chen F et al (151) had used comprehensive analysis of untargeted/ targeted serum metabolomics and metagenome sequencing of paired fecal samples to develop a model based on changes in gut microbiomeassociated serum metabolites (GMSM) that can distinguish patients with CRC and adenoma from healthy normal individuals better than the clinical marker carcinoembryonic antigen. Similarly, Clos-Garcia et al (19) used an integration of metabolomics and microbiome data analysis to find possible biomarkers for both advanced adenomas (AD) and CRC from feces samples.…”
Section: Metabolomics Discloses Crc Biomarkers Associated With Gut Floramentioning
confidence: 99%
“…To research host-microbe interactions as well as the etiology of CRC, including discovering new treatment targets and the microbiota that distinguishes diseased intestines from those of healthy persons, an integrated investigation of metabolomics and gut metabolic activity is required. Even though most research has discovered dynamic changes in intestinal microbiota composition, gene abundance, and metabolites throughout the multi-stage development of CRC (9,151,152), more study is required to fully comprehend the biological mechanism that goes beyond simple association analyses. Because the data on food or drug intervention is mainly obtained from observational research, much further comprehensive longitudinal prospective analyses on specific metabolites, as well as innovative technical advances, are needed to assess whether intestinal microbial and metabolites directly induce tumorigenesis and causality of medicine action.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%